Feasibility study of measuring $$b→ sγ $$ b → s γ photon polarisation in $$D^0→ K_1(1270)^- e^+ν _e$$ D 0 → K 1 ( 1270 ) - e + ν e at STCF - Yu-Lan Fan (SpringerOpen, 2021)
Abstract We report a sensitive study of measuring $$b→ sγ $$ b → s γ photon polarisation in $$D^{0}→ K_1(1270)^-e^+ν _e$$ D 0 → K 1 ( 1270 ) - e + ν e with an integrated luminosity of $$\mathscr {L}$$ L = 1 ab $$^{-1}$$ - 1 at a center-of-mass energy of 3.773 GeV at a future Super Tau Charm Facility. More than 61,000 signals of $$D^{0}→ K_1(1270)^-e^+ν _e$$ D 0 → K 1 ( 1270 ) - e + ν e are expected. Based on a fast simulation software package, the statistical sensitivity for the ratio of up-down asymmetry is estimated to be $$1.5× 10^{-2}$$ 1.5 × 10 - 2 by performing a two-dimensional angular analysis in $$D^{0}→ K_1(1270)^-e^+ν _e$$ D 0 → K 1 ( 1270 ) - e + ν e . Combining with measurements of up-down asymmetry in $$B→ K_1γ $$ B → K 1 γ , the photon polarisation in $$b→ sγ $$ b → s γ can be determined model-independently.